Efektivitas Layanan Bimbingan dan Konseling Melalui Pendekatan Komprehensif dalam Meningkatkan Kesejahteraan Psikologis dan Prestasi Akademik Siswa - Rahmatunnida, Rahmatunnida; Nurhidayah, Mawarni; Akmali, Raga Ziqri; Marja, Marja (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2024)
This study aims to examine the effectiveness of guidance and counseling services through a comprehensive approach in improving students' psychological well-being and academic achievement. The comprehensive approach includes individual, group, and holistic program development to meet students' emotional, social, and academic needs. This research uses a qualitative method with a description analysis approach. Primary data were obtained from observation and direct observation of counseling guidance services at the school. And interviews with counseling teachers, special assistant teachers, children with special needs, and regular children. While secondary data is obtained from the results of literature searches such as books, documentation and journals that have the same relevance as this research. After the data is obtained and grouped according to its type, then after analyzing the data with descriptive analysis to describe the findings of this study as a whole. The results showed that guidance and counseling services through a comprehensive approach significantly improved students' psychological well-being and academic achievement. The findings suggest that the application of a comprehensive approach in guidance and counseling services is essential to support students' holistic development and improve the quality of education.